2016
DOI: 10.1007/s12035-016-9761-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cold Inducible RNA-Binding Protein in Severe Hypoxia-Induced Growth Arrest of Neural Stem Cells In Vitro

Abstract: Neonatal hypoxia is the leading cause of brain damage with birth complications. Many studies have reported proliferation-promoting effect of mild hypoxia on neural stem cells (NSCs). However, how severe hypoxia influences the behavior of NSCs has been poorly explored. In the present study, we investigated the effects of 5, 3, and 1 % oxygen exposure on NSCs in vitro. MTT, neurosphere assay, and 5-ethynyl-2′-deoxyuridine (EdU) incorporation revealed a quick growth arrest of C17.2 cells and primary NSCs induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 44 publications
6
35
0
Order By: Relevance
“…Each of these proteins was significantly upregulated in RTT tissue relative to WT. In particular, cold-inducible RNA-binding protein (CIRBP), an RNA-binding protein upregulated in response to hypoxia [ 70 ], shows one of the largest fold increases in our data set (4.3-fold; Table 2 ). Interestingly, this protein has previously been shown to be upregulated in RTT tissue [ 21 ], although mRNA levels do not appear to be affected ([ 71 ] and our data).…”
Section: Resultsmentioning
confidence: 99%
“…Each of these proteins was significantly upregulated in RTT tissue relative to WT. In particular, cold-inducible RNA-binding protein (CIRBP), an RNA-binding protein upregulated in response to hypoxia [ 70 ], shows one of the largest fold increases in our data set (4.3-fold; Table 2 ). Interestingly, this protein has previously been shown to be upregulated in RTT tissue [ 21 ], although mRNA levels do not appear to be affected ([ 71 ] and our data).…”
Section: Resultsmentioning
confidence: 99%
“…NSCs are mainly reserved in the subventricular zone, and the region of subventricular zone is at its maximum size at neonatal stage (Zerlin, Levison, & Goldman, ). Substantial evidence has reported that neurons and oligodendrocytes suffer apoptotic status under hypoxia condition (Tan, Guo, & Liu, ; Zhang et al, ). Considering that NSCs are the major cell type that can regenerate lost nerve cells, we explored the potential therapeutic drug for HIE in hypoxia‐treated NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…NSCs are mainly reserved in the subventricular zone, and the region of subventricular zone is at its maximum size at neonatal stage (Zerlin, Levison, & Goldman, 1995). Substantial evidence has reported that neurons and oligodendrocytes suffer apoptotic status under hypoxia condition (Tan, Guo, & Liu, 2013;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, both mild (8 %) and severe (1 %) hypoxia can induce CIRP and RBM3 expression to a comparable level by a mechanism that involves neither hypoxia-inducible factor (HIF) nor mitochondria in vitro [ 54 ]. In contrast, severe hypoxia mimicking ischemia in an in vitro model applying cultured neural stem cells (NSCs) suppresses CIRP expression in parallel with cell cycle arrest [ 55 ]. Since hydrogen peroxide treatment can inhibit the hypothermia-induced expression of CIRP [ 56 , 57 ] and a mild level of reactive oxygen species (ROS) is beneficial, whereas a high level is toxic for NSC proliferation, it has been hypothesized that mild hypoxia resulting in mild elevation of ROS increases CIRP expression, whereas severe hypoxia/ischemia inducing an overload of ROS suppresses CIRP expression [ 55 ].…”
Section: Stress-regulated Expressionmentioning
confidence: 99%
“…In contrast, severe hypoxia mimicking ischemia in an in vitro model applying cultured neural stem cells (NSCs) suppresses CIRP expression in parallel with cell cycle arrest [ 55 ]. Since hydrogen peroxide treatment can inhibit the hypothermia-induced expression of CIRP [ 56 , 57 ] and a mild level of reactive oxygen species (ROS) is beneficial, whereas a high level is toxic for NSC proliferation, it has been hypothesized that mild hypoxia resulting in mild elevation of ROS increases CIRP expression, whereas severe hypoxia/ischemia inducing an overload of ROS suppresses CIRP expression [ 55 ]. Exposing pregnant mice in late gestation to severe systemic hypoxia causes overexpression of HIF-dependent genes and downregulation of RBM3 expression in the placenta and developing brain [ 58 ].…”
Section: Stress-regulated Expressionmentioning
confidence: 99%